OPTIONS FOR REGULATING LABOR IN THE GIG ECONOMY: WHAT ARE THEY? - Supriadi, Dedi; Saprizon, Saprizon; Putri, Aslina; Wirnawan, Frendli; Afandi, Ahmad; Alpian, Alpian; Fikri, KMS. Novyar Satriawan (Yayasan Education and Social Center, 2025)
Traditional labor regulations and employment standards are complicated by the features of paid work associated with digital platform businesses, such as taxi, delivery, and maintenance roles. This article evaluates the scope of this. The types of employment in Indonesia and their primary attributes subsequently examine the relevance of current employment regulations to these gig jobs, referencing Australian and international legislation and jurisprudence. Significant ambiguity exists over the extent of conventional legislation, minimum requirements, and remedies in the domain of irregular digitally mediated employment. Regulators and legislators should evaluate methods to enhance and broaden the regulatory framework overseeing gig work. The article identifies five principal options: enforcing current laws, clarifying or broadening definitions of 'employment,' establishing a new category of 'independent workers,' granting rights to 'workers' rather than employees, and reevaluating the notion of an 'employer.' We evaluate the advantages and disadvantages of these methods and encourage authorities to use innovative and ambitious strategies to enhance the minimum standards and conditions for workers in these circumstances